The early sociology of management and organizations. - Sheldon, Oliver (Taylor & Francis e-Library, 2004)
Taylorism was criticised for its over-simplistic view of what motivated the worker. Oliver Sheldon's theme was that though Taylorism had helped the development of a science of management, such work should not detract from the predominantly human job of the manager to manage. His work prefigures the human relations approach to management theory of Elton Mayo and F.J. Roethlisberger in rejecting the notion that economic incentives largely explain employee behaviour.